Pengembangan Media Wayang Berbahan Barang Bekas Berbasis Budaya Lingkungan Setempat Bermuatan Cerita Rakyat Bengkulu Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - Erna Oksari; Abdul Muktadir (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to develop wayang media made from used goods based on local environmental culture that imposes Bengkulu folklore to improve learning outcomes for fourth grade elementary school students. This type of research is research and development or Research and Development (R&D). The results of this study indicate that 1. Implementation was carried out at SDN 101 North Bengkulu to measure and describe the effectiveness of wayang media activities that had been developed. 2. The validation results on the design aspect obtained an average Aiken's V score of 0.88 (Very Valid) with an average validator agreement of 0.80% (Almost Perfect). The validation results on the language aspect obtained an average Aiken's V score of 0.89 (Very Valid) with an average validator agreement of 0.93% (Almost Perfect). 3. Wayang media made from used goods based on local environmental culture which contains Bengkulu folklore in class IV fiction text material is considered to be able to improve student learning outcomes.